The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijms20246324
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Gene Regulatory Networks in Chondrocytes

Abstract: Chondrogenesis is a key developmental process that molds the framework of our body and generates the skeletal tissues by coupling with osteogenesis. The developmental processes are well-coordinated by spatiotemporal gene expressions, which are hardwired with gene regulatory elements. Those elements exist as thousands of modules of DNA sequences on the genome. Transcription factors function as key regulatory proteins by binding to regulatory elements and recruiting cofactors. Over the past 30 years, extensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…In addition, we found both the chondroblastic and osteoblastic malignant cells were localized in the primary site while only the uniformed osteoblastic malignant cells were detected in the lung metastasis lesions of the chondroblastic OS of patient BC17, suggesting that the osteoblastic OS cells have more aggressive tumoral activities and are capable of distant metastasis compared to the corresponding chondroblastic tumor cells. This is supported by the reports that the malignant chondroblastic cells grew slow and were less sensitive to the chemotherapy treatments than malignant osteoblastic cells 71 . These results suggested that chemotherapy reagents that targeting both the chondroblastic and osteoblastic tumor cells are warranted for efficient treatment for chondroblastic OS in clinic.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, we found both the chondroblastic and osteoblastic malignant cells were localized in the primary site while only the uniformed osteoblastic malignant cells were detected in the lung metastasis lesions of the chondroblastic OS of patient BC17, suggesting that the osteoblastic OS cells have more aggressive tumoral activities and are capable of distant metastasis compared to the corresponding chondroblastic tumor cells. This is supported by the reports that the malignant chondroblastic cells grew slow and were less sensitive to the chemotherapy treatments than malignant osteoblastic cells 71 . These results suggested that chemotherapy reagents that targeting both the chondroblastic and osteoblastic tumor cells are warranted for efficient treatment for chondroblastic OS in clinic.…”
Section: Discussionsupporting
confidence: 68%
“…Since SOX9 heterozygous mutations were linked to campomelic dysplasia, a perinatally lethal skeletal malformation disease (12,13), studies in model systems have revealed that SOX9 is a master chondrogenic transcription factor (14,15). It may not be a pioneer factor opening chromatin at specific loci, but it potently transactivates PC genes and thereby drives embryonic chondrogenesis (16)(17)(18)(19).…”
Section: Significancementioning
confidence: 99%
“…SOX9 defects in humans lead to campomelic dysplasia characterized by major defects in cartilage and bone [ 10 ]. Although much is understood about how SOX9 regulates cartilage matrix synthesis and hence joint function, less is known about the mechanisms controlling its own expression [ 11 , 12 ]. Some evidence suggests that miR-145 targets and suppresses the expression of Sox9, inhibiting chondrogenic differentiation of murine embryonic mesenchymal cells, as well as critically affecting human articular chondrocyte function [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%